2013
DOI: 10.1517/14656566.2013.823949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salmeterol xinafoate plus fluticasone propionate for the treatment of chronic obstructive pulmonary disease

Abstract: Until new forms of drug combinations are made available, the use of dual-therapy containing a LABA and ICS remain as the most logical and appropriate approach for the treatment of patients suffering from severe and very severe COPD with repeated exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Salmeterol, a β2-receptor agonist, is recommended as a long-acting bronchodilator for patients with COPD (36). Restrepo et al (8) identified that salmeterol xinafoate and fluticasone propionate treatment improved the survival rate of patients with severe COPD. In addition, Ryan et al (37) indicated that salmeterol also improved nocturnal sleeping arterial oxygen saturation and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmeterol, a β2-receptor agonist, is recommended as a long-acting bronchodilator for patients with COPD (36). Restrepo et al (8) identified that salmeterol xinafoate and fluticasone propionate treatment improved the survival rate of patients with severe COPD. In addition, Ryan et al (37) indicated that salmeterol also improved nocturnal sleeping arterial oxygen saturation and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Salmeterol and formoterol are two commonly used drugs in COPD therapy, which act as β2-receptor agonists (8). Salmeterol and formoterol were identified as β2-receptor agonists that inhibit early and late phase antigen-induced airway hyper-responsiveness (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Different research groups have been focused on the key inflammatory regulators, such as inhibitors of phosphodiesterase-4 (PDE4), p38 mitogen-activated protein kinase (p38), and Janus kinases [10][11][12][13].…”
Section: Development Of New Drugs For Chronic Obstructive Pulmonary Dmentioning
confidence: 99%